The effects of the application of the Internet and information and communication technologies in the field of tourism mediation - Clide Rodríguez Vázquez; Lorena Rodríguez Campo; Valentín Alejandro Martínez Fernández; Magdalena Rodríguez Fernández (The International Journal of Management Science and Information Technology (IJMSIT), 2016)
Over the years tourism mediation has experienced major changes, including the arrival of the Internet and the application of Information and Communication Technologies (ICTs). The principal aim of this communication is to analyse the transformation of the travel agency subsector in the light of the changes that have occurred following the application of ICTs. By virtue of the nature of the research, a qualitative methodology was used, consisting of in-depth interviews with managers working in physical, online and franchise travel agencies and tour operators present in Galicia. The conclusions reached corroborated that the means used by tourism consumers to access information has changed following the application of ICTs, leading to situations of tourism "de-mediation" and "remediation" and impacting considerably on the role played by travel agencies in the chain of value
Keywords: 650; Tourism mediation; ICTs; the Internet; Travel agencies